Constructing the Politics of Cookery: Authorial Strategy and Domestic Politics in English Cookery Books, 1655-1670 - Saffitz, Claire (Cuizine, 2013)
This essay argues that authors of English cookery texts in the 1650s, sixties, and seventies debated not only changing ideas and behaviors surrounding cooking, service, and feasting, but were also participating in a renegotiation and redefinition of other Restoration subjects such as public versus private spaces, domesticity, gender roles, and social class. This article considers five cookery texts published between the years 1656 and 1670: two works of royalist propaganda that adopted the form of the cookery book, The Queens Closet Opened (1656), attributed to Henrietta Maria, and The Court & Kitchin of Elizabeth (1664), attributed to Elizabeth Cromwell; two works by professional male cooks, The Accomplisht Cook (1661) by Robert May, and The Whole Art of Cookery Dissected (1661) by William Rabisha; and The Queen-Like Closet (1670) by Hannah Wolley, England’s first professional female writer and cookery book author.In these works, domestic spaces and activities – as well as the emerging form of the cookery text itself – become a sort of battleground on which men and women vied to construct and defend their authority as culinary experts and authors of printed cookery books. Simultaneously, these authors were actively engaged in a debate about English nationhood in the Restoration and what kinds of people could or should participate in the politics of good housekeeping.